IMPLEMENTASI KEBIJAKAN PENGELOLAAN LIMBAH DI PELABUHAN TANJUNG PERAK SURABAYA (Studi Implementasi Peraturan Menteri Negara Lingkungan Ilidup Nomor 05 Tahun 2009) - Bonifasius Giantara Andjioe; Nuhman; Agus Subianto (Faculty of Social and Political Science, 2014)
Research on implementation of waste management policies at the port of Tanjung Perak Surabaya (case study implementation of the environment state minister Regulation number 05 of 2009) aims to describe and analyze port waste management policy implementation and analyze the factors that support and hinder the successful implementation of waste management port. Research using qualitative research methods. To determine the waste management policy implementation at the Port of Tanjung Perak port Surabaya, researchers used the theory George Edward III with variable Communication Research. Resources, Disposition and Bureaucratic Structure. and requirements of the executive, while the reality in the field, still found the implementation of waste management is done by certain elements illegally. This condition would be detrimental to the State considering the international waste management port is also supervised by the world body IMO (International Maritime Organisation), this condition will affect the confidence of foreign parties, if this is not resolved, resulting in performance of port. While the structure of the bureaucracy of the party appointed to implement port waste management, namely PT. IPC Marine Service (PMSj is still not fully able to implement them on their own: these activities are still carried along Primkopal Koarmatim and partnership with PT. Petro Gas Main East Java. This gives rise to high costs. Hazardous waste management facility owned PT.PMS B3 still not received operating licenses for unfinished environmental impact assessment, the position of the facility located in the port area which is veiy risky to the port environment. Waste management in the port of Tanjung Perak Surabaya already he done with some supporting the disposition issued by the various stakeholders involved, while the factors that are supporting budget and limited of supervisor We hope the facility for the Tanjung Perak port will achieve to be best International Port in the future.